Laboratorio de ciencia interactiva con wix para la enseñanza – aprendizaje de la dinámica en la asignatura de física, en los estudiantes de 2º año de bachillerato de la Unidad Educativa Comunitaria Intercultural Bilingüe “Surupucyu” en el periodo 2024 – 2025. - Argüello Guizado, Andreé Romario (2025)
The implementation of digital tools, digital teaching resources, and interactive laboratories for teaching physics has become a challenge for the Ecuadorian education system. Considering the rural context in which this research was conducted, the effort and commitment of teachers and students, which are needed to implement new teaching models, is even more significant. This research work has been carried out at the Bilingual Intercultural Community Educational Unit "Surupucyu", and aims to strengthen the teaching-learning process of Dynamics, based on the use of an interactive science laboratory with Wix, in which digital tools, digital teaching resources and interactive laboratories are integrated for teaching Dynamics, which allow students to understand theoretical concepts, practical applications and the correct development of exercises. The methodology used is a mixed approach, a convergent quasi-experimental design, and an applied approach. Different techniques were used for data collection, including interviews, surveys, pretests, and posttests. These techniques provided valuable insights and allowed us to verify whether the use of the different components of the interactive science lab improved students' academic performance. Finally, it can be concluded that an interactive science lab developed on the Wix platform can complement the teaching methodology proposed by the teacher and generate meaningful learning. Statistically, it has been proven that changing methodologies and integrating other teaching resources improve and transform the teaching process, creating a more participatory, practical, and motivating classroom environment.